Integration and design of a reconfigurable reflectarray antenna with an RF LoRa-based system for IoT multi-protocol applications - Sousa, Daniel Carvalho de (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.